"Cuba, Nicaragua, Unidas Vencerán": Official Collaborations between the Sandinista and Cuban Revolutions. Issue 4 (October 2021) - Snyder, Emily
Abstract: The Cuban and Sandinista Revolutions stand together as Latin America's two socialist revolutions achieved through guerrilla insurgency in the latter half of the twentieth century. But beyond studies that demonstrate that Cuba militarily trained and supported the Sandinistas before, during, and after their guerrilla phase, and observations that the two countries were connected by the bonds of socialist revolution, the nature of Cuba and Nicaragua's revolutionary relationship remains little explored. This article traces exchanges of people and expertise between each revolutionary state's Ministry of Foreign Relations and Ministry of Culture. It employs diplomatic and institutional archives, personal collections, and oral interviews to demonstrate the deep involvement of Cuban experts in building the Sandinista state. Yet, Cuban advice may have exacerbated tensions within Nicaragua. This article also shows that tensions marked the day-to-day realities of Cubans and Nicaraguans tasked with carrying out collaborations, revealing their layered and often contradictory nature. Illuminating high-level policy in terms of Cuban-Nicaraguan exchanges and how they unfolded on the ground contributes to new international histories of the Sandinista and Cuban revolutions by shifting away from North-South perspectives to focus instead on how the Sandinistas navigated collaboration with their most important regional ally.